Is the oil price a determinant of employment in oil intensive romanian communities? - Alexandra Horobet; Vlad-Cosmin Bulai (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: The purpose of this study is to determine the resilience of oil intensive Romanian communities to oil price fluctuations. Design/methodology/approach: The methodology employed is based on identifying the communities with the most extensive oil extraction activities using GIS (Geographic Information System) software. We then apply a random effects panel regression model to check the significance of the oil price as a predictor of employment. Finding: Results indicate that the effect of oil price fluctuations is limited, with employment in the identified communities following the national trend. Research limitations/implications: Unfortunately, our study is hindered by data availability issues and a short time series. Nevertheless, conclusions are backed by the country's characteristics - a diversified economy, integration with refining operations, and the presence of related manufacturing and services activities. Originality/value: The study adds to the existing literature by focusing on a mature region with a long history of hydrocarbon extraction activities. We argue that the study of local communities in mature regions is of great importance in the context of the ongoing energy transition, particularly of those located within the European Union.
Keywords: O13; Q32; Q35; 330; random effects; oil; resource curse; local community